2022
DOI: 10.1111/itor.13224
|View full text |Cite
|
Sign up to set email alerts
|

Network polarization, filter bubbles, and echo chambers: an annotated review of measures and reduction methods

Abstract: Polarization arises when the underlying network connecting the members of a community or society becomes characterized by highly connected groups with weak intergroup connectivity. The increasing polarization, the strengthening of echo chambers, and the isolation caused by information filters in social networks are increasingly attracting the attention of researchers from different areas of knowledge such as computer science, economics, and social and political sciences. This work presents an annotated review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 123 publications
(252 reference statements)
0
4
0
Order By: Relevance
“…a subgraph that contains all vertices in A i and all edges between vertices in A i ), then the modularity value Q for this single group will be equal to zero [29]. A previous study showed that there is a lack of consolidated group-level measures for evaluating polarization [21].…”
Section: Modularity and Contribution Of Groups To Polarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…a subgraph that contains all vertices in A i and all edges between vertices in A i ), then the modularity value Q for this single group will be equal to zero [29]. A previous study showed that there is a lack of consolidated group-level measures for evaluating polarization [21].…”
Section: Modularity and Contribution Of Groups To Polarizationmentioning
confidence: 99%
“…They have attracted millions of individuals by allowing them to communicate, share their ideas, and discuss different topics, being an excellent tool for studying individual and group behavior. However, polarization and hostility are increasingly shifting from social media to the real world, as it was demonstrated by several political events, such as the protests of the Yellow Vest movement in France in 2018, the protests after George Floyd's death in 2020, the US Capitol attack in 2021, and the convoy protests in Canada in 2022 [21].…”
Section: Introductionmentioning
confidence: 99%
“…In Matlab environment, this paper simulates the performance of gray coded BOTDA sensor under different noise influences [21]. Firstly, this paper constructs a mathematical model for simulation, which considers the case that the frequency difference between pump light and probe light is 10.684GHz.…”
Section: The Influence Of Polarization Random Noise and Its Suppressi...mentioning
confidence: 99%
“…Measures of polarization proposed in the literature depend on the system that is being investigated (Interian et al, 2023). Most analyses focus on political parties and parliaments.…”
Section: Introductionmentioning
confidence: 99%